WRITING A NEW POETRY WITH TANDUR STEPS: LEARNING USING QUANTUM LEARNING METHOD ASSISTED IN ICT - Selvia Yuliana (IKIP Siliwangi, 2022)
Learning based on the background of student ability to write new poetry is low. Based on the evaluation results, writing poetry does not reach the indicators of success in writing poetry. The research aims to determine the scenario and implementation, teacher and student responses, as well as to determine the difficulties experienced by grade X Vocational High School students in completing tasks of writing new poetry using the Quantum Learning method assisted by ICT media. This study uses a qualitative description method. The results of the study: (1) The learning scenario consisted of five meetings, namely four treatments using the Quantum Learning method with TANDUR (Grow, Experience, Name, Demonstrate, Repeat, and Celebrate) steps assisted by ICT media (powtoon and kahoot) and one test, the results of the implementation of learning get the percentage of teacher and student observations of 97.5% and 97.8% and can improve the ability to write new poetry by getting an average score of 82.